(untitled) (Journal of Pharma Insights and Research, 2024)
Bell’s palsy, a common peripheral facial nerve paralysis, presents as acute unilateral facial weakness without an identifiable cause. This case report describes a 74-year-old male with type 2 diabetes mellitus who presented to the outpatient department with sudden-onset right-sided facial deviation and slurred speech. The patient had a similar episode 40 years ago and was currently on oral hypoglycemic medications for diabetes management. Clinical examination revealed right-sided facial weakness with normal vital signs. Laboratory investigations, including serum electrolytes, thyroid profile, and complete blood count, were within normal limits. Magnetic Resonance Imaging showed bilateral age-related cerebral and cerebellar atrophy with grade I chronic small vessel ischemia. The patient was treated with a combination of oral acyclovir, prednisolone, and supportive medications. Physical therapy, including electrical stimulation of facial muscles and facial exercises, was initiated under professional supervision. The patient showed significant improvement during the three-week hospital stay and continued to recover during the six-month follow-up period. This case highlights the importance of prompt medical intervention, comprehensive treatment approach, and the role of physiotherapy in Bell’s palsy management. The favorable outcome in this elderly patient with comorbid diabetes mellitus demonstrates that appropriate medical management combined with rehabilitation can lead to successful recovery, even in complex cases